HEAT CAPACITY OF SYNTHETIC HYDROUS MG-CORDIERITE AT LOW TEMPERATURES: THERMODYNAMIC PROPERTIES AND THE BEHAVIOR OF THE H2O MOLECULE IN SELECTED HYDROUS MICRO AND NANOPOROUS SILICATES - Paukov I.E.; Kovalevskaya Y.A.; Rahmoun N.-S.; Geiger C.A. (My University, 2007)
The heat capacity, Cp, of a synthetic hydrous cordierite of composition Mg1.97Al3.94Si5.06 O18 · 0.625H2O was measured for the first time using precise adiabatic calorimetry in the temperature range from 6 to 300 K. Hydrous Mg-cordierite was obtained by hydrothermal treatment of anhydrous Mg-cordierite (Paukov et al. 2006) at 4 kbar and 600 °C for 24 hours. The synthetic product was characterized using X-ray diffraction and powder IR spectroscopy. Rietveld refinement gives a = 17.060(2) Å, b = 9.721(1) Å, and c = 9.338(1) Å with V = 1548.7(3) Å3 and Δ = 0.25, and the IR spectrum shows only the presence of Class I-Type I H2O in the channel cavities. Small Cp anomalies were observed at 272.98 ±0.03 K and 239.43 ±0.13 K, which are thought to be related to very small amounts of H2O occurring in tiny fluid inclusions and to surface H2O, respectively. From the heat-capacity data on hydrous Mg-cordierite, various thermodynamic functions were calculated and are presented in table form. The calculated partial molar entropy for one mole of H2O in hydrous Mg-cordierite at 298.15 K and 1 bar is 80.5 J/(mol·K). The partial molar volume for H2O in hydrous Mg-cordierite at 298 K and 1 bar is zero. The Cp results, together with published heat-capacity data on three different zeolites, permit a comparison and analysis of their heat-capacity behavior. The heat-capacity behavior of H2O molecules in zeolites is more similar to that of ice at T < 300 K and not to gaseous H2O, which can be attributed to the presence of hydrogen-bonded H2O molecules. In contrast, the heat-capacity behavior for the "quasi-free" H2O molecule in cordierite is more similar to that of a free H2O molecule in the gaseous state between approximately 100 and 300 K. At T < 100 K, the energies of low-energy modes, especially external H2O translations, determine heat-capacity behavior. Model heat capacities for H2O in cordierite were calculated using the Einstein model and using as input data the results from inelastic neutron-scattering measurements on hydrous Mg-cordierite (Winkler and Hennion 1994). Reasonable agreement between experiment and calculations can be achieved using three H2O translational modes, one of which is hypothetical, and two librational H2O modes. The experimental spectra do not appear to show all six external H2O modes and further vibrational spectroscopic study is required to determine their energies. At T > 300 K, the heat capacity for H2O is the smallest in steam with values increasing in hydrous beryl and cordierite, to H2O in various zeolites, and finally to liquid H2O. This behavior may reflect the nature of the hydrogen bonding and the energies of internal H2O stretching modes, which decrease in energy with increasing hydrogen-bonding strength in the various systems.
Keywords: ADIABATIC CALORIMETRY; H2O MOLECULE; HEAT CAPACITY; HYDROUS MG-CORDIERITE; MICRO AND NANOPOROUS SILICATES